A retrospective matched cohort single‐center study evaluating outcomes of COVID‐19 and the impact of immunomodulation on COVID‐19‐related cytokine release syndrome in solid organ transplant recipients. Issue 2 (22nd January 2021) - Ringer, Matthew; Azmy, Veronica; Kaman, Kelsey; Tang, Daiwei; Cheung, Harry; Azar, Marwan M.; Price, Christina; Malinis, Maricar
Abstract: This retrospective matched cohort study describes 30 solid organ transplant (SOT) patients with Coronavirus Disease 2019 (COVID‐19) matched 1:2 to 60 non‐SOT patients (control group) based on age, body mass index (BMI), and comorbidities (hypertension and diabetes mellitus with hemoglobin A1c > 8.0%). The SOT group had a higher proportion of cardiovascular disease ( P  < .05). During the index hospitalization, there were no significant differences with regard to disease severity or critical care needs (mechanical intubation, vasopressors, and renal replacement therapy). At 28 days, 4 (13%) patients died in the SOT group and 8 (13%) patients died in the control group ( P  = 1.0). Nineteen patients received tocilizumab in the SOT group compared to 29 patients in the control group. Among these patients, interleukin‐6 (IL‐6) and soluble interleukin‐2 receptor (sIL2R) levels increased after tocilizumab and interleukin‐10 (IL‐10) levels decreased after tocilizumab. Overall, SOT patients had comparable mortality to non‐SOT patients, although numerically more SOT patients received tocilizumab (63% vs 48%) and steroids (37% vs 20%). Larger, multi‐center studies are needed to ascertain these findings. Lastly, the complex cytokine release syndrome in COVID‐19 remains an area of intense research and the analysis of key interleukin levels (IL‐6, IL‐10, and sIL2R) in this study contributes to the understanding of this process.